THE SPECIFICS OF HYPERTROPHIC CARDIOMYOPATHY CLINICAL PRESENTATION IN PATIENTS WITH VARIOUS MUTATIONS OF SARCOMERE GENES - S. M. Komissarova; N. N. Chakova; S. S. Niyazova; S. V. Kazakov; E. A. Zhukova; A. V. Aleksandrov; O. S. Glotov; A. S. Glotov (Российский кардиологический журнал)
Aim. The assessment of clinical presentation of HCMP in patients having mutations of the sarcomere protein genes.Material and methods. In 11 patients with hypertrophic cardiomyopathy (HCMP) we performed analysis of clinical and instrumental data and search for mutations of coding sequences of the genes ACTC1, MYBPC3, MYH7, MYL2, MYL3, TNNI3, TNNT2 и TPM1 via the sequencing method (next-generation sequencing (NGS).Results. The clinical presentation is described, of HCMP, and the analysis provided of the complications development during the period of follow-up of the patients with genes coding sarcomere proteins: Arg403Trp, Lys847del and Arg1712Trp (gene MYH7); Gln1233Term, Trp1214Arg, Arg502Gln, Arg326Gln and Ser236Gly (gene MYBPC3); Arg58Gln in gene MYL2.Conclusion. The revealed mutations in sarcomere genes in patients with HCMP are associated with early clinical onset of the disease, with worse family anamnesis and development of complications during follow-up.